Comparing environmental awareness between chemistry education students and non-chemistry education students. (February 2020) - Ridha, I; Hasan, M; Sulastri
Abstract: This study aimed to determine the level of environmental awareness including knowledge, attitudes and behaviour about the environment between chemistry education students and non-chemistry at the Teacher Training and Education Faculty of Universitas Syiah Kuala. The type of research used was descriptive quantitative with analytical survey method. The research respondents were second-semester students in chemistry, physics, and geography and history study programs. The sample was selected using non-probability sampling technique with the type of purposive sampling. The number of respondents was 100. Data was collected using a questionnaire. Data analysis was conducted using descriptive statistics. The results showed that the level of environmental awareness of chemistry education students was lower than non-chemical education students, except in the knowledge variable. This results could be due to the lack of implementation of environmental education in chemical learning materials. In chemistry education tends to strengthen the cognitive domain compared to affective (attitude) and psychomotor (behaviour).